Operational performance of an Aerossolo prototype - Lopes, Afonso [UNESP] (2010)
It is been a great deal of interest the studying of the operational performance of tractors and its machinery especially in work conditions. The present study had as objective to evaluate the operational performance of an Aerossolo prototype tracked with a Valtra BM100 4x2 TDA, with the engine power of 73.6 kW (100 cv). The prototype equipment is a drag type, hydraulically commanded, with telescopic heading for longitudinal adjustment, two lateral sections with 28 knifes in each one of them, concrete ballasts, wheels of transport and aggregate breaker coil. The work was conducted in the Department of Agricultural Engineering of the UNESP, Jaboticabal Campus, in a randomized blocks design, factorial 3 x 3, with four repetitions. The nine studied treatments were a combination for three ballast conditions (0; 960 and 1,307 kg) and three angles of the sections (0o; 7o and 14o). The results indicate an increase in operational consumption (liters per hectare) of 32.4% in relation to the concrete ballast addition, and a 26.8% in relation to the angle variation between sections. The working depth, traction force and power demands were higher with the increases in the concrete ballast and the angle variation between sections.